Transient elastography predicts fibrosis progression in patients with recurrent hepatitis C after liver transplantation. Issue 6 (24th January 2008) - Rigamonti, C; Donato, M F; Fraquelli, M; Agnelli, F; Ronchi, G; Casazza, G; Rossi, G; Colombo, M
Abstract : Objective: Transient elastography (TE) allows non-invasive evaluation of the severity of liver disease in patients with chronic hepatitis C. This procedure, however, warrants further validation in the setting of liver transplantation (LT), including patients under follow-up for recurrent hepatitis C. Setting: Tertiary referral hospital. Patients: 95 patients (75 males) transplanted for end-stage liver disease due to hepatitis C virus. Interventions: Paired liver biopsy (LB) and TE were carried out 6–156 (median, 35) months after LT. 40 patients with recurrent hepatitis C sequentially evaluated 6–21 months apart. Main outcome measures: Clinical, laboratory and graft histological features influencing TE results. Results: Median TE values were 7.6 kPa in the 90 patients with a successful TE examination, being 5.6 kPa in the 30 patients with Ishak fibrosis score (S) of 0–1, 7.6 kPa in the 38 with S2–3; 16.7 kPa in the 22 with S4–6, (p<0.0001). Areas under the ROC curves were 0.85 (95% CI, 0.76 to 0.92) for S⩾3, 0.90 (95% CI, 0.82 to 0.95) for S⩾4 with 7.9 and 11.9 kPa optimal TE cut-off (81% and 82% sensitivity, 88% and 94% negative predictive value, respectively). Fibrosis, necroinflammatory activity and higher than 200 IU/l gamma-glutamyl transpeptidase levels independently influenced TE results. During post-LT follow-up, TE results changed in parallel with grading (r = 0.63) and staging (r = 0.71), showing 86% sensitivity and 92% specificity in predicting staging increases. Conclusions: TE accurately predicts fibrosis progression in LT patients with recurrent hepatitis C, suggesting that protocol LB might be avoided in patients with improved or stable TE values during follow-up.